2011
DOI: 10.1111/j.1365-2095.2011.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

A study on dietary l-lysine requirement of juvenile yellow catfish Pelteobagrus fulvidraco

Abstract: An 8-week feeding trial was conducted to determine lysine requirement of juvenile yellow catfish (Pelteobagrus fulvidraco) by feeding formulated diets containing crystalline L L-lysine.Six isonitrogenous and isoenergetic diets (405 g kg )1 protein, 18 kJ g )1 gloss energy) containing fish meal together with soybean protein concentrate as protein sources and fish oil together with soybean oil as lipid sources were formulated. Crystalline L L-lysine was added into the six diets to acquire lysine concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
5
33
0
1
Order By: Relevance
“…In the present study, the whole‐body composition of GIFT tilapia was not affected ( p > .05) by dietary lysine supplementation. This result corresponds well to the different studies of Cao et al (), Khan () and Li, Zhou, Mo, Pan, and Gan (), where dietary lysine supplementation had no significant ( p > .05) differences in the whole‐body composition in yellow catfish, stinging catfish and juvenile grass carp, respectively. In general, it is considered that the whole‐body amino acid profiles do not change in fish under different treatments and even between species.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the whole‐body composition of GIFT tilapia was not affected ( p > .05) by dietary lysine supplementation. This result corresponds well to the different studies of Cao et al (), Khan () and Li, Zhou, Mo, Pan, and Gan (), where dietary lysine supplementation had no significant ( p > .05) differences in the whole‐body composition in yellow catfish, stinging catfish and juvenile grass carp, respectively. In general, it is considered that the whole‐body amino acid profiles do not change in fish under different treatments and even between species.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it plays an important role in the synthesis of carnitine, which is important for the transport of long‐chain fatty acids into the mitochondrion for energy generation. In addition, dietary supplementation of lysine improves feed utilization (Li et al, ), nitrogen retention (Cao et al, ) and also reduce body lipid content of fish (Burtle & Liu, ; Nguyen, Rønnestad, Buttle, Lai, & Espe, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study significant enhancements in plasma total protein level was observed at increased isoleucine levels. There is no available study on the effect of dietary isoleucine on fish plasma total protein level, but in agreement to our study significant enhancements in fish serum/plasma protein levels have been reported following administration of optimum dietary lysine level in black sea bream (Sparus macrocephalus) (Zhou et al, 2010) and yellow catfish (Pelteobagrus fulvidraco) (Cao et al, 2012), and optimal dietary valine level in red sea bream (Rahimnejad and Lee, 2013). In general, ALT and AST are mainly distributed in the liver and spleen and play important roles in protein metabolism.…”
Section: Discussionsupporting
confidence: 79%
“…Broken‐line “segmented” analysis of SGR indicates that juvenile dusky kob require dietary lysine of 31.7 g/kg dry diet to maximize growth performance. The dietary requirement of 31.7 g/kg dry diet equates to 73.5 g/kg dietary protein, which was lower than the reported value for black sea bream Sparus macrocephalus , 87.1 g/kg dietary protein (Zhou, Shao, Xu, Ma, & Xu, ) and yellow catfish Pelteobagrus fulvidraco , 83.2 g/kg dietary protein (Cao et al., ). This value is higher than the values reported for other commonly cultured fishes (Wilson, ).…”
Section: Discussionmentioning
confidence: 73%